2021
DOI: 10.3390/cancers13164020
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs Correlate with HLA Expression in Uveal Melanoma: Both Up- and Downregulation Are Related to Monosomy 3

Abstract: MicroRNAs are known to play a role in the regulation of inflammation. As a high HLA Class I expression is associated with a bad prognosis in UM, we set out to determine whether any miRNAs were related to a high HLA Class I expression and inflammation. We also determined whether such miRNAs were related to the UM’s genetic status. The expression of 125 miRNAs was determined in 64 primary UM from Leiden. Similarly, the mRNA expression of HLA-A, HLA-B, TAP1, BAP1, and immune cell markers was obtained. Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A study conducted by Souri et al compared the expressions of HLA and miRNA in the same tumors using mRNA expression with four unlined HLA Class I probes [ 88 ]. The study showed that one cluster of miRNAs was positively matched with HLA Class I and infiltrating leukocytes, while the other showed the opposite effect.…”
Section: Mirna and Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Souri et al compared the expressions of HLA and miRNA in the same tumors using mRNA expression with four unlined HLA Class I probes [ 88 ]. The study showed that one cluster of miRNAs was positively matched with HLA Class I and infiltrating leukocytes, while the other showed the opposite effect.…”
Section: Mirna and Uveal Melanomamentioning
confidence: 99%
“…The study also confirmed the relationship between both miRNA expression patterns and chromosome 3 (BAP1) status in UM. This finding could be the starting point to consider miRNAs as regulators of inflammation in UM, regulated by BAP1 [ 88 ].…”
Section: Mirna and Uveal Melanomamentioning
confidence: 99%
“…Both miRNAs expression patterns in UM show a relation are to chromosome 3/BAP1 status. This study could be the starting point to consider the miRNAs as regulators of inflammation in UM, regulated by BAP1 ( 138 ).…”
Section: Genomic Abnormalities In Uveal Melanomamentioning
confidence: 99%
“… miR-146a [ 97 ] Upregulated in metastatic patients Plasma RT-PCR miR-155 [ 97 ] Upregulated in metastatic patients Plasma RT-PCR Is upregulated in UM-tumors and promotes invasion and proliferation by targeting Nedd4-family interactive protein 1 (NDFIP1). NDFIP1 is necessary for ubiquitination and translocation of, tumor suppressor, PTEN [ 116 , 117 , 118 ]. Upregulation is correlated to monosomy 3 status [ 118 ].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…NDFIP1 is necessary for ubiquitination and translocation of, tumor suppressor, PTEN [ 116 , 117 , 118 ]. Upregulation is correlated to monosomy 3 status [ 118 ]. miR-155 [ 94 ] Downregulated in UM-patients VH and VH EVs TLDA miR-181a [ 97 ] Downregulated in metastatic patients Plasma RT-PCR Upregulation inhibits CTD small phosphatase like (CTDSPL) expression, which in turn promotes cell cycle progression in UM cells [ 119 ].…”
Section: Liquid Biopsymentioning
confidence: 99%